Analisis Pengawasan Direktorat Jenderal Pajak atas Transparansi Pelaporan PPh Orang Pribadi Pengguna Kripto - Anastasia, Anastasia; Budi Saptono , Prianto (Jurnal Ilmiah Administrasi Publik, 2023)
The imposition of tax on crypto after the issuance of PMK 66 of 2023 with significant revenue realization requires in-depth supervision. This research aims to analyze the control by the DJP regarding transparency regarding the PIT reporting of crypto users. The research theory is the Supervision Theory. The analysis uses qualitative and secondary data collection techniques through literature studies and government agency documentation. The research results show that supervision by the DJP is carried out through CRMBI, exchangers, crypto tax reporting, and collaboration with relevant government institutions in optimizing crypto asset transaction monitoring data. This research concludes that the modernization of supervision by the DGT has been well-designed and implemented in stages. Based on the conclusions of the study that has been carried out, these findings provide suggestions for optimizing supervision for the DJP to prepare an integrated taxation system when reporting crypto users' Annual Income Tax Returns with innovative tax reporting feature applications from exchangers and implementing CRMBI specifically for the crypto asset transaction business process.